Determining The Legal Status Of Successors To Exclusive Rights According To The Legislation Of The Republic Of Kazakhstan - Asilkhanovna Jumabayeva, Karlygash; Furkatovna Tatarinova, Lola; Tursunovna Alayeva, Gulnaz; Zhusupbekovna Suleimenova, Saule; Vladimirovich Tatarinov, Danila (Opción, 2019)
The article analyzes the inheritance of exclusive rights common to all legal systems. Although there are certain national and international laws in the field of exclusive rights, many disputes arise due to the imperfection of leg- islative provisions and the absence of legal wishes expressed by testators. If the transfer of exclusive rights from the testator (author) to their heirs or other copyright holders is properly planned, it will enable better control over selecting subjects of hereditary legal relations, namely who will own and manage the author’s intellectual property after their death. This need is conditioned by the fact that the person who inherits exclusive rights to some copyrighted work after the author’s death can further use it. However, it is necessary to clarify that inherited rights cannot be realized to the fullest extent as if the author could have done it. In this regard, law enforcers face a serious problem of determining the legal status of successors to exclusive rights. Based on the study conducted, the authors of the article have elabo- rated recommendations to improve the mechanism for limiting human rights and freedoms, as well as ensuring their effective protection.